North Korean refugee health in South Korea (NORNS) study: study design and methods - Lee Yo; Lee Won; Kim Yun; Cho Myong; Kim Joo; Lee Yun; Kim Hee; Choi Dong; Kim Sin; Robinson Courtland (BMC Public Health, 2012)
Abstract Background Understanding the health status of North Korean refugees (NKRs), and changes in health during the resettlement process, is important from both the humanitarian standpoint and the scientific perspective. The NOrth Korean Refugee health iN South Korea (NORNS) study aims to document the health status and health determinants of North Korean refugees, to observe various health outcomes as they occur while adapting to the westernized lifestyle of South Korea, and to explain the mechanisms of how health of migrants and refugees changes in the context of new environmental risks and opportunities. Methods The NORNS study was composed of an initial survey and a follow-up survey 3.5 years apart. Participants were recruited voluntarily among those aged 30 or more living in Seoul. The survey consists of a health questionnaire and medical examination. The health questionnaire comprises the following six domains: 1) demographic and migration information 2) disease history, 3) mental health, 4) health-related lifestyle, 5) female reproductive health, and 6) sociocultural adaptation. The medical examination comprises anthropometric measurements, blood pressure and atherosclerosis, and various biochemical measurements. Prevalence of several diseases able to be diagnosed from the medical examination, the changes between the two surveys, and the association between the outcome and other measurements, such as length of stay and extent of adaptation in South Korea will be investigated. Furthermore, the outcome will be compared to a South Korean counterpart cohort to evaluate the relative health status of NKRs. Discussion The NORNS study targeting adult NKRs in South Korea is a valuable study because various scales and medical measurements are employed for the first time. The results obtained from this study are expected to be utilized for developing a health policy for NKRs and North Korean people after unification. Additionally, since NKRs are an immigrant group who are the same race and have the same genetic characteristics as South Koreans, this study has the characteristics of a unique type of migrant health study.